GAMBARAN PERILAKU BULLYING PADA SISWA SD N PADUKUHAN PUNGKURAN PLERET BANTUL - Bety Agustina Rahayu; Debby Yulianthi Maria; Riza Yulina (Journal of Nursing Invention, 2020)
Background: Bullying is an act of using power to hurt others, both verbally, physically, and psychologically so that the victim feels depressed, traumatized and helpless. The increasing prevalence of bullying cases in the school environment shows an increase. This problem has become everyone's problem not only for the victim. Everyone's concern about bullying cases is needed so that acts of violence such as bullying do not occur. Purpose: this study aims to determine the description of bullying behavior at SDN Pungkuran Pleret Bantul. Method: This study is a quantitative descriptive study using a cross sectional design. The population in this study were students of SDN Pungkuran Pleret Bantul. The sampling technique used purposive sampling with inclusion and exclusion criteria, namely students in grades 4, 5 and 6 who were willing to become research respondents. A total of 102 students participated in this study. This study uses a questionnaire instrument that has been tested for validity and reliability. Test analysis using the chi-square. Results: A total of 69 (67.65%) students were included in moderate level of bullying behavior and 33 (32.35%) students did low level bullying. Chi square correlation test results obtained p-value for gender (0.108) and age (0.070)> 0.05, which means that there is no relationship between sex and age with bullying behavior. Conclusion: The majority of students at SD N Pungkuran Pleret Bantul are categorized as moderate bullying. There is no relationship between gender and age with bullying behavior among students at SDN Pungkuran Pleret Bantul. Latar Belakang: Bullying merupakan tindakan penggunaan kekuasaan untuk menyakiti orang lain, baik secara verbal, fisik, maupun psikologis sehingga korban merasa tertekan, trauma, dan tidak berdaya. Prevalensi peningkatan kasus bullying di lingkungan sekolah menunjukkan peningkatan. Masalah ini telah menjadi masalah semua orang tidak hanya bagi korban saja. Kepedulian semua orang tentang kasus bullying diperlukan agar tidak terjadi tindakan kekerasan semacam bullying. Tujuan: penelitian bertujuan untuk mengetahui gambaran perilaku bullying di SDN Pungkuran Pleret Bantul. Metode: Penelitian ini merupakan penelitian deskriptif kuantitatif yang menggunakan rancangan cross sectional. Populasi dalam penelitian ini adalah siswa SDN Pungkuran Pleret Bantul. Teknik pengambilan sampel menggunakan purposive sampling dengan kriteria inklusi dan eksklusi yaitu siswa kelas 4, 5 dan 6 yang bersedia menjadi responden penelitian. Sebanyak 102 siswa yang mengikuti penelitian ini. Penelitian ini menggunakan instrument kuesioner yang telah diuji validitas dan reliabilitas. Uji analisis menggunakan chi-square. Hasil: Sebanyak 69 (67,65%) siswa termasuk dalam perilaku bullying tingkat sedang dan 33 (32,35%) siswa melakukan bullying tingkat rendah. Hasil uji korelasi chi square didapatkan p-value pada jenis kelamin (0,108) dan umur (0,070) > 0,05 yang artinya tidak ada hubungan jenis kelamin dan umur dengan perilaku bullying. Kesimpulan: Mayoritas siswa SD N Pungkuran Pleret Bantul termasuk dalam perilaku bullying tingkat sedang. Tidak ada hubungan antara jenis kelamin maupun umur dengan perilaku bullying pada siswa SDN Pungkuran Pleret Bantul.